Prevalence And Risk Factors For Postnatal Depression In Sabah, Malaysia: A Cohort Study - Aza Sherin Mohamad Yusuff; Li Tang; Colin W Binns; Andy H Lee (Elsevier, 2024)
Women and Birth Volume 28, Issue 1, March 2015, Pages 25-29